Visible-Light-Mediated C–H Functionalization via Photoredox Catalysis: A Mechanistic Investigation and Synthetic Applications - Dr. Kamalesh Kumar Patel (International Journal of Scientific Research in Chemistry, 2025)
The development of mild, sustainable, and efficient C–H bond functionalization strategies has significantly advanced modern organic synthesis. In this study, we report a visible-light-mediated approach to direct C–H functionalization using photoredox catalysis. Employing [Ir(dF(CF₃)ppy)_2(dtbbpy)]PF₆ as the photocatalyst under blue LED irradiation, a wide range of arenes, alkylarenes, and heterocycles underwent selective C–H bromination under ambient conditions. Reaction optimization revealed that the combination of MeCN as solvent and AcOH as an additive led to high yields and regioselectivity, particularly favoring para-substitution in electron-rich arenes and benzylic bromination in alkylarenes. Radical trapping, Stern–Volmer analysis, and kinetic isotope effect (KIE) studies confirmed a radical mechanism initiated by oxidative quenching of the photocatalyst by N-bromosuccinimide (NBS). A primary KIE of 3.1 highlighted C–H bond cleavage as the rate-determining step. Density functional theory (DFT) calculations supported the proposed mechanism by revealing favorable energy barriers and stable radical intermediates. The method showed high tolerance toward functional groups and was scalable to multigram synthesis without yield deterioration. Despite decreased efficiency with unactivated sp³ C–H bonds and electron-deficient arenes, the strategy presents a valuable platform for late-stage functionalization and further mechanistic exploration. This work provides key mechanistic insight and demonstrates the synthetic potential of photoredox-driven C–H functionalization as a green and practical tool in organic chemistry.